Benign Neurofibroma/Schwannoma Hybrid Peripheral Nerve Sheath Tumor of the Ulnar Nerve Harboring a Metastatic Papillary Thyroid Carcinoma Deposit: A Case Report of Tumor-to-Tumor Metastasis. (14th December 2022) - Colazo, Juan M.; Perez, Alexander N.; Judice, Anthony D.; Quirion, Julia; Prieto-Granada, Carlos N.; Holt, Ginger E.
Abstract : A 74-year-old man with a medical history significant for papillary thyroid cancer (PTC) presented with a rapidly enlarging grape-sized mass in his right medial arm with paresthesia in the ulnar nerve distribution. Imaging was suspicious for a peripheral nerve sheath tumor (PNST), but an ultrasound-guided biopsy was equivocal. The mass was excised with final histopathology demonstrating a benign neurofibroma/schwannoma hybrid nerve sheath tumor (N/S HNST) harboring a metastatic PTC deposit, ultimately mimicking the rare glandular schwannoma subtype. Next-generation sequencing (NGS) of the lesion demonstrated somatic variants in BRAF and TERT (common in PTC) and NF2 (common in PNSTs). After excision, the patient's nerve symptoms improved. A postsurgical PET/CT scan also showed progression in the lungs/mediastinum. Due to the metastatic nature of his PTC, he was treated with 14 mg of Lenvima (lenvatinib) daily, and his PET/CT surveillance was performed at more frequent intervals. Tumor-to-tumor metastasis (TTM) is a rare occurrence. To our knowledge, this is the first case reported on PTC metastasizing into a benign (hybrid) PNST, which mimicked glandular schwannoma. Symptomatology, imaging characteristics, NGS, and histopathological characteristics that can decipher between different benign PNST subtypes (schwannoma, neurofibroma, glandular, hybrid, etc.), malignant PNSTs (MPNSTs), and TTM are described.